2017
DOI: 10.1002/ange.201709564
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Polymeric Nanocubes by Self‐Assembly and Crystallization of Dithiolane‐Containing Triblock Copolymers

Abstract: Template-free fabrication of non-spherical polymeric nanoparticles is desirable for various applications,b ut has had limited success owing to thermodynamic favorability of sphere formation. Herein we present as imple way to prepare cubic nanoparticles of blockcopolymers by self-assembly from aqueous solutions at room temperature.Nanocubes with edges of 40-200 nm are formed spontaneously on different surfaces upon water evaporation from micellar solutions of triblock copolymers containing ac entral poly(ethyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…19 Waymouth et al prepared nanocubes via selfassembly combined with crystallization of dithiolane-containing BCPs. 16 In these systems, the nanocubes were obtained through traditional BCP self-assembly in solution coupled with additional interactions such as crystallization. In our work, the polymeric cuboids were formed in large synthetic scale in a PISA formulation, in which azobenzene-containing monomers form a LC core-forming block.…”
Section: Acs Macro Lettersmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Waymouth et al prepared nanocubes via selfassembly combined with crystallization of dithiolane-containing BCPs. 16 In these systems, the nanocubes were obtained through traditional BCP self-assembly in solution coupled with additional interactions such as crystallization. In our work, the polymeric cuboids were formed in large synthetic scale in a PISA formulation, in which azobenzene-containing monomers form a LC core-forming block.…”
Section: Acs Macro Lettersmentioning
confidence: 99%
“…11 Block copolymer (BCP) selfassembly in solution is an effective approach to polymeric NPs with different morphologies. 13,14 Moreover, additional interactions, such as crystallization, 15,16 liquid crystalline (LC) ordering, 17,18 and poly(ionic liquid), 19 were introduced into BCP for the design and preparation of anisotropic morphologies. However, a scalable synthetic method that can enable the synthesis of anisotropic NPs at high solids remains a great challenge via this approach.…”
mentioning
confidence: 99%
“… 67 69 In addition, these observations are inconsistent with those reported in previous studies, in which it was shown that pDdeTC-PEG-pDdeTC triblock copolymers self-assembled in water into bridged flower-like micelles, which in turn efficiently crosslinked through ring-opening polymerizations of the dithiolanes initiated by the addition of a thiol. 37 , 40 , 42 These and our studies differ in the experimental setup and composition of the copolymers used. To exclude the possible impact of the former on the result, we repeated the same method as reported in ref ( 42 ) (described in Figure S13 , Supporting Information), i.e ., direct hydration of p(CL 9 -DdeTC 3.1 )-PEG (entry 15, Table 1 ) and pDdeTC 5 -PEG (entry 16, Table 1 ), to reach polymer concentrations of 10 and 20 mg/mL, respectively, followed by ring-opening polymerization of the dithiolanes initiated by 3,6-dioxa-1,8-octanedithiol and thiol capping by maleimide.…”
Section: Resultsmentioning
confidence: 87%
“…41). 156 These cyclic carbonates were subjected to ROP using PEG (14 kg mol −1 ) as a divalent macroinitiator to fabricate amphiphilic ABA-type triblock polymers with an M n = 16.9–18.2 kg mol −1 ( Đ = 1.13–1.18). These polymers then underwent self-assembly in aqueous solution to form flower-like micelles, with the asparagusic acid-derived hydrogels displaying greater dynamic properties, adaptability, and self-healing than those derived from lipoic acid.…”
Section: Miscellaneousmentioning
confidence: 99%